OC-034 Cortical and Brainstem Neurophysiological Mechanisms underlying Dysphagia in Parkinson'S Disease: A Transcranial Magnetic Stimulation Study' 'On' and 'Off' Levodopa. (4th June 2013) - Michou, E; Harris, L; Hamdy, S
Abstract : Introduction: Dysphagia in Parkinson's disease (PD) patients, persisting despite dopaminergic medication, affects nutritional and drug intake with reduced quality-of-life (Michou & Hamdy, Exp Rev Neurother 2010). Here we explore the potential neurophysiological mechanisms underlying dysphagia in PD when 'on' and 'off' Levodopa with transcranial magnetic stimulation (TMS). Methods: 26 verified PD patients (65 ± 8 yoa, 10 male) completed the Swallowing Disturbance Questionnaire (Manor et al Mov Dis 2007) and SWAL-QOL (McHorney et al Dysphagia 2002). After 12 hours 'off' L-dopa, patients underwent a) cortical TMS mapping for pharyngeal musculature, b) brainstem reflexes TMS stimulation, c) lung function tests with spirometry before and after (d) videofluroscopy (VFS) of liquid, pureed boluses and saliva. These were repeated following the administration of L-dopa to the patients. Factorial and non-parametric statistical tests were applied. Results: VFS identified dysphagia in 10 patients (Group A), while 6 patients showed swallowing difficulties only 'On-L-dopa'(Group B), with the remainder 10 subjects being non-dysphagic (Group C). Swal-QOL score was reduced in Group A (p < 0.05), while aspiration-penetration scores (thin and puree consistencies) and additional 'clearing swallows' worsened after administration of L-dopa (p < 0.05) for Group B. After Levodopa intake, cortical pharyngeal excitability was decreased significantly in Group A (p < 0.005), but increased in Group C (p < 0.001) compared to 'off-state' (Figure 1 ). No significant change in lung function was observed during the off-or on-state, nor did lung function correlate with dysphagia. The amplitudes of the brainstem reflexes were different between the 3 groups 'on-Levodopa'. Patients experiencing dysphagia only when on Levodopa (Group B) showed significant decrease (inhibition) in brainstem reflexes amplitude after Levodopa. Conclusion: Different patterns of cortical and brainstem activity, reflecting different mechanisms of compensation with Levodopa intake, can differentiate dysphagic PD groups. Moreover, physiology was negatively affected by L-dopa in groups with inhibition of brainstem reflexes. Our novel brain stimulation data demonstrate the dysphagia in PD patients is associated with altered cortical and brainstem activity, modulated by L-dopa differentially across the PD groups, providing the platform for research on rehabilitation for dysphagia in PD. Disclosure of Interest: None Declared